Lipid-based berberine loaded lyophilized nanomicelles with enhanced antioxidant effect: Design and characterization - Rakesh Mishra, Akash Aher (Journal of Applied Pharmaceutical Science, 2024)
Berberine (BERB), an isoquinoline alkaloid, is widely reported for its versatile pharmacological potential mainly due to its excellent antioxidant activity. However, solubility and permeability concerns limit its bioavailability resulting in a marked decrease in antioxidant prospective and subsequent therapeutic effects. The current work aimed to design BERB-loaded lyophilized nanomicelles formulations to enhance their antioxidant potential. Thin-film hydration technique was employed to develop BERB-loaded nanomicelles using ethanol as a solvent and Gelucire 44/14 and 50/13 were screened as a polymer stabilizer. A 32-factorial design was adopted to investigate the impact of the polymer: drug proportion along with stirring speed. The optimized batch of BERB nanomicelles formulation was also further lyophilized to improve the stability of prepared batches. Nanomicelles batches showed the size of particle and entrapment efficiency in the range of 69 ± 1.57 to 576 ± 1.73 nm and 61.84% ± 1.96% to 87.34% ± 1.88 %, respectively. The designed optimized nanomicelles system showed nearly 5-fold enhancement in the aqueous solubility with 2.38-fold enhancement in percent ex-vivo drug permeation compared with the drug. The drug nanomicelles formulation showed enhanced percentage peroxidation reduction and 2,2-diphenyl-1-picrylhydrazyl inhibition (81.12 ± 1.21; 73.12 ± 2.07) compared to the pure drug (31.99 ± 1.32; 38.71 ± 2.07). The obtained BERB-loaded lyophilized nanomicelles with enhanced antioxidant activity could be efficiently explored for their diverse potential therapeutic properties.
Keywords: Berberine, nanomicelles, solubility, permeability, lyophilization, antioxidant